Effect of whole-body cryotherapy on recovery after high-intensity training in elite rowers - Huang, T.; Dan, L.; Wang, W.; Ren, J.; Liu, X.; Li, J. (Frontiers in Physiology, 2024)
The purpose of this study was to investigate the effect of whole-body cryotherapy (WBC) on acute recovery after a single high-intensity training day. Twelve elite professional male rowers from the national aquatic training base. They were randomly divided into a WBC group (n = 6) and a control group (CON group, n = 6). They performed a high-intensity training program, with a single session immediately followed by WBC (-110°C, 3 min) or recovered naturally for 3 min (CON group). Rowing performance, skin temperature, heart rate, blood pressure, and blood lactate concentrations were recorded before training, immediately, 5 min, and 15 min after the intervention. Blood samples were collected early in the morning of the day of intervention and that of the following day. The results indicated that 1) the blood lactate concentrations after WBC were significantly lower than pre-training (p < 0.05); 2) the maximum power significantly decreased immediately after WBC compared to pre-training (p < 0.05); 3) a significant main effect of time was observed for average speed, which significantly decreased after WBC (p < 0.05); 4) a significant main effect of time for blood parameters was observed. Specifically, hematocrit, cortisol, and hemoglobin were significantly lower after WBC than pre-intervention, whereas testosterone/cortisol was significantly higher than pre-intervention (p < 0.05). The results of this study showed that a single session of WBC had a positive effect on accelerating the elimination of blood lactate after HIT, but did not significantly change rowing performance and physiological parameters. A single session of WBC was not an effective strategy for elite rowers for acute recovery after HIT.